Data‐Driven Supply Chain Orientation and Financial Performance: The Moderating Effect of Innovation‐Focused Complementary Assets. (8th May 2019) - Yu, Wantao; Jacobs, Mark A.; Chavez, Roberto; Feng, Mengying
Abstract: Drawing on the complementary assets framework, this study explores the moderating effect of innovation‐focused complementary assets (CA‐I) on the relationship between a data‐driven supply chain orientation (DDSCO) and firm financial performance. To test the moderating effect, survey data gathered from 329 manufacturing firms in China were analysed using a moderated regression analysis. The results indicate that DDSCO has a significant positive effect on financial performance, and that capabilities for product and process innovation function as complementary assets moderating the DDSCO–performance relationship. The findings suggest that innovation‐focused complementary assets are performance differentiators when paired with a DDSCO and explain why some firms obtain financial benefits from the development of a DDSCO while others do not. Specifically, competitive advantage from a DDSCO may not be realized unless CA‐I and potentially other complementary assets are harnessed, thus providing useful practical guidance to managers. Hence, the study provides empirical support for the complementary assets framework.